Efficient microwave to optical photon conversion: An electro-optical realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G. L. (Optica, 2016)
Linking classical microwave electrical circuits to the optical telecommunication band is at the core of modern communication. Future quantum information networks will require coherent microwave-to-optical conversion to link electronic quantum processors and memories via low-loss optical telecommunication networks. Efficient conversion can be achieved with electro-optical modulators operating at the single microwave photon level. In the standard electro-optic modulation scheme, this is impossible because both up- and down-converted sidebands are necessarily present. Here, we demonstrate true single-sideband up- or down-conversion in a triply resonant whispering gallery mode resonator by explicitly addressing modes with asymmetric free spectral range. Compared to previous experiments, we show a 3 orders of magnitude improvement of the electro-optical conversion efficiency, reaching 0.1% photon number conversion for a 10 GHz microwave tone at 0.42 mW of optical pump power. The presented scheme is fully compatible with existing superconducting 3D circuit quantum electrodynamics technology and can be used for nonclassical state conversion and communication. Our conversion bandwidth is larger than 1 MHz and is not fundamentally limited.
CRIS-Team Scopus Importer:2021-06-29

Efficient single sideband microwave to optical conversion using a LiNbO3 WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dimitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (2016 Conference on Lasers and Electro-Optics, CLEO 2016, 2016)
We present a coherent microwave to telecom signal converter based on the electro-optical effect using a crystalline WGM-resonator coupled to a 3D microwave cavity, achieving high photon conversion efficiency of 0.1% with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Nonlinear single sideband microwave to optical conversion using an electro-optic WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2016)
Nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band is achieved within a crystalline whispering gallery mode resonator, reaching 0.1% photon number conversion efficiency with MHz bandwidth.
CRIS-Team Scopus Importer:2021-06-29

Single sideband microwave to optical photon conversion-an electro-optic realization - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry V.; Marquardt, Christoph; Fink, Johannes M.; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald G.L. (Optics InfoBase Conference Papers, 2017)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator.
CRIS-Team Scopus Importer:2021-06-29